2016
DOI: 10.7727/wimj.2016.230
|View full text |Cite
|
Sign up to set email alerts
|

Salivary IgA and Total Protein in Human Subjects with Oral Lichen Planus and Squamous Cell Carcinoma

Abstract: Purpose: The purpose of this study was to compare salivary immunoglobulin A (IgA) and total protein (TP) in patients suffering from oral lichen planus (OLP) and oral squamous cell carcinoma (OSCC), against healthy control. Methods: In a case-control study, 20 patients with OSCC, 30 patients suffering from OLP and 50 non-involved subjects were enrolled. The mean stimulated and unstimulated saliva IgA and TP levels were assayed by the Biuret method and immunoturbidometry respectively. Statistical analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…They raised the hypothesis that mutations in the p53 gene might be involved in malignant transformation and suggested that p53 overexpression might be an indicator of malignant transformation [ 46 ]. A recent study also revealed a higher expression of p53 in the saliva of patients with OSCC than in those with OLP [ 47 ]. Crosthwaite et al suggested that benign lesions that are positive for p53 should be carefully monitored [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…They raised the hypothesis that mutations in the p53 gene might be involved in malignant transformation and suggested that p53 overexpression might be an indicator of malignant transformation [ 46 ]. A recent study also revealed a higher expression of p53 in the saliva of patients with OSCC than in those with OLP [ 47 ]. Crosthwaite et al suggested that benign lesions that are positive for p53 should be carefully monitored [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…One of the genes activated in response to several stress stimuli such as oncogene activation and DNA damage is p53 [ 44 ]. Immunohistochemical analysis revealed that there are over 60% OSCC patients with higher expression of p53, and the concentration of p53 of OSCC patients in saliva was significantly higher than in healthy participants [ 45 , 46 ]. Previous studies have shown that IQ inhibits cell growth in colon cancer by increasing p-p53 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the p53 positivity was significantly higher in reticular form (47%) than in erosive form (23%). [ 43 ] In addition, another study proposed that higher expression levels of P53 and p21 in OLP samples compared to normal tissues may indicate the precancerous potential of OLPs. [ 44 ] Besides, Bcl-2 positivity was found in 23.3% of OSCC samples and 19.9% of the OLP samples.…”
Section: Discussionmentioning
confidence: 99%